Determination of Anaerobic Threshold by a new approach through the incremental exercise using proportion in HR and Ve changes in rowers - Lachezar G. Stefanov; Svilen E. Neykov (IP Iermakov S.S., 2021)
Background and Study Aim. The aim of this research is to create a non-invasive and easy to apply in practice approach to determine the anaerobic threshold based only on measurement of the pulmonary ventilation and the hearth rate. It uses proportions, with which these variables were changed during a maximal incremental test. Material and Methods. Twenty athletes from the national rowing team of Bulgaria with average age of 17.5 years were tested. Participants performed a one-time graded incremental exercise test to exhaustion on a rowing ergometer. The proposed new approach for determining the anaerobic threshold is related to detecting the power. Thus, one curve (obtained from differences in percentages of hearth rate and pulmonary ventilation) crosses the other one (obtained from pulmonary ventilation in percentages). The crossing point corresponds to the anaerobic threshold. This approach was compared with two methods determining the lactate threshold, by blood lactate measurement. Results. The Shapiro-Wilk test results indicated, that the samples of the heart rate of the compared methods have a normal or close to the normal distribution. The Fisher's F-test demonstrated, that the standard deviations of the samples do not differ significantly two by two at ɑ=0.05. The Bland&Altman test presented, that the 95% of all measurement data points lie within the confidence interval limit for each of the comparisons made between the new approach and two methods. Conclusions. Our proposed approach is non-invasive and can be easily applied in the field conditions, without using gas-analysing devices. In addition, it is reliable, reproducible and comparable to the accepted for "Gold Standard" methods for determination of anaerobic threshold with 95% statistical significance.